A new contact detection algorithm for non-spherical particles in the Discrete Element Method - Boon, C; Houlsby, G; Utili, S (2011)
Houlsby (2009) presented the concept of "potential particles", a method for modelling non-circular particles for the Discrete Element Method (DEM). Potential particles can assume a wide variety of shapes, ranging from circular to almost polygonal in 2-D and from spherical to almost polyhedral in 3-D. Here we present a new algorithm for the contact detection between potential particles in both 2-D and 3-D. The contact detection problem is formulated into a Second-Order Cone Program (SOCP) and solved using the commercial optimization software MOSEK (MOSEK, 2010). The algorithm is suitable for both rounded and angular particles, and was found to be robust in a variety of situations. Two 3-D simulations are illustrated using the new algorithm.